RANCANG BANGUN APLIKASI DASHBOARD UNTUK VISUALISASI TRANSAKSI EKSPOR PADA PT. KELOLA MINA LAUT - Listiany, Heny; Wibowo, Januar; Rahmawati, Endra (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
PT. Kelola Mina Laut is a company engaged in the seafood industry. The company has been exporting processed products to several countries including: USA, Canada, Europe, Russia, Japan etc.The company's goal is to achieve a target value of export transactions by year. To determine the attainment of the objectives of the company divisions and the related directors always conduct regular meetings. However, the data presented at the meeting is still shaped table data and just in the previous period, so it does not correspond to the needs of the board of directors for the data tables presented uninformative and real time.Visualization Dashboard Application for Export Transactions on PT. Kelola Mina Laut is a software that can provide the information value of the ratio of export transactions by year, by state, by product category and by customer with the target at a certain period in real time. Information is presented in a visual form such as pie charts, rod and line. This application is built for ease of directors and marketing division in knowing the difference between the value export transaction with a target value of exports in a given period.